2014
DOI: 10.1080/1060586x.2014.918452
|View full text |Cite
|
Sign up to set email alerts
|

The nature of anti-immigrant sentiment in post-socialist Russia

Abstract: The main aim of this study was to investigate whether the competition and cultural theoretical models that have received solid empirical support in the context of Western European societies can explain anti-foreigner sentiment in post-socialist Russia as a society searching for new national identity borders. Data obtained from the third round of the European Social Survey (2006) indicate a high level of anti-foreigner sentiment in contemporary Russia -more than 60% of Russians claimed that immigrants undermine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
4
22
0
2
Order By: Relevance
“…Hagendoorn et al noted that it was also found in other countries and that "a common element in these hierarchies is that After incorporating all the individual level predictors and accounting for regional heterogeneity our models leave about 95% of the outcome variance unexplained. This is consistent with the results reported previously by Gorodzeisky et al (2014) who noticed a much weaker predictive power of the models explaining attitudes towards immigrants in Russia compared to other European countries. Individual socio-economic characteristics that are standard in sociological research fail to structure the attitudes of Russians, and knowing a person's sex, age, level of education, occupation, ethnicity and location provides us with very little information about their views on immigration.…”
Section: Resultssupporting
confidence: 93%
“…Hagendoorn et al noted that it was also found in other countries and that "a common element in these hierarchies is that After incorporating all the individual level predictors and accounting for regional heterogeneity our models leave about 95% of the outcome variance unexplained. This is consistent with the results reported previously by Gorodzeisky et al (2014) who noticed a much weaker predictive power of the models explaining attitudes towards immigrants in Russia compared to other European countries. Individual socio-economic characteristics that are standard in sociological research fail to structure the attitudes of Russians, and knowing a person's sex, age, level of education, occupation, ethnicity and location provides us with very little information about their views on immigration.…”
Section: Resultssupporting
confidence: 93%
“…Stratifikační teorie přikládá význam zejména diskriminaci cizinců na trhu s bydlením, jež vede k segmentaci realitního trhu a stratifikaci čtvrtí ve městě podle dostupnosti cizincům [Brown, Chung 2008;Walton 2012]. V postsocialistické společnosti potvrzují nezanedbatelný význam antiimigračních postojů studie z Ruska [Gorodzeisky, Glikman, Maskileyson 2015], Maďarska [Bimbi 2011], Polska [Meuleman, Davidov, Billiet 2009] či Česka [Burjanek 2001]. Prokázána byla též etnická diferenciace trhu s bydlením [Hess, Tammaru, Leetmaa 2012], restrikce vůči nabývání nemovitostí cizinci [Hodgson, Cullinan, Campbell 1999; Gürlich 2011] a jiné diskriminační praktiky majitelů bytů vůči cizincům [Šmídová, Šafr 2009].…”
Section: Teoretická Východiska: Migrace Cizinců Do Postsocialistickéhunclassified
“…A number of previous studies used survey data to explore attitudes towards immigrants in Russia. Antiimmigrant sentiment is stronger in Russia than in most other European countries, whereas the explanatory power of the models that try to predict attitudes towards immigrants with the indicators of socio-economic position and the attitudinal variables is much lower (Gorodzeisky, Glikman and Maskileyson, 2015;Bessudnov, 2016), although explanations based on group threat and economic competition theories cannot be dismissed (Bahry, 2016). Ethnic Russians are on average more negative about immigrants than ethnic minorities (Gorodzeisky and Glikman, 2017), and the opposition towards immigration is often based on racial prejudice (Gorodzeisky, 2019).…”
Section: The Russian Contextmentioning
confidence: 99%